Pengaruh Peringatan Visual Iklan Kemasan Rokok: Pengukuran Tingkatan Perasaan Takut yang Dibedakan Berdasarkan Jenis Kelamin dan Usia - Mayasari, Mayasari; Sudarjat, Hadi; Sholih, Mally G. (Jurnal Politikom Indonesiana, 2018)
Cigarettes kill nearly seven million people every year throughout the world. Changes in cigarette packaging design is one way to reduce the number of smokers in the community. Some studies suggest that the threat to cigarette packaging in the form of Threatening Visual Warnings (TVWs) only has a slight effect and does not have any effect at all on the reaction and character of people who smoke. In contrast, several studies have shown that TVWs have a positive effect on smokers’ desire to smoke or reduce smoking consumption. Because of these conflicting results, further research is needed. The main objective of this study was to assess the effectiveness of cigarette packaging images in terms of emotional and behavioral reactions, namely TVWs at moderate vs. very high levels of cigarette packaging for active smokers by age and sex category. The age group is divided into adolescents (12-17 years) and adults (> 18 years). The sex group is divided into two, namely male and female. From the results of chi-square statistical analysis, it was obtained a significant correlation or influence between the threat level of moderate level and high level on cigarette packaging to the feeling of fear or disgust among smokers, namely in the category of adolescent girls, adolescent boys and men (p- value <0.05). Whereas in adult women there is no significant effect (p-value> 0.05). Keywords: Threatening Visual Warnings, Smokers, Ads, Health